Evaluation of target coverage and margins adequacy during CyberKnife Lung Optimized Treatment. Issue 4 (12th March 2018) - Ricotti, Rosalinda; Seregni, Matteo; Ciardo, Delia; Vigorito, Sabrina; Rondi, Elena; Piperno, Gaia; Ferrari, Annamaria; Zerella, Maria Alessia; Arculeo, Simona; Francia, Claudia Maria; Sibio, Daniela; Cattani, Federica; et al.
Abstract : Purpose : Evaluation of target coverage and verification of safety margins, in motion management strategies implemented by Lung Optimized Treatment (LOT) module in CyberKnife system. Methods: Three fiducial‐less motion management strategies provided by LOT can be selected according to tumor visibility in the X ray images acquired during treatment. In 2‐view modality the tumor is visible in both X ray images and full motion tracking is performed. In 1‐view modality the tumor is visible in a single X ray image, therefore, motion tracking is combined with an internal target volume (ITV)‐based margin expansion. In 0‐view modality the lesion is not visible, consequently the treatment relies entirely on an ITV‐based approach. Data from 30 patients treated in 2‐view modality were selected providing information on the three‐dimensional tumor motion in correspondence to each X ray image. Treatments in 1‐view and 0‐view modalities were simulated by processing log files and planning volumes. Planning target volume (PTV) margins were defined according to the tracking modality: end‐exhale clinical target volume (CTV) + 3 mm in 2‐view and ITV + 5 mm in 0‐view. In the 1‐view scenario, the ITV encompasses only tumor motion along the non‐visible direction. Then, non‐uniform ITV to PTV margins were applied: 3 mm and 5 mm in the visible and non‐visible direction, respectively. We defined the coverage of each voxel of the CTV as the percentage of X ray images where such voxel was included in the PTV. In 2‐view modality coverage was calculated as the intersection between the CTV centred on the imaged target position and the PTV centred on the predicted target position, as recorded in log files. In 1‐view modality, coverage was calculated as the intersection between the CTV centred on the imaged target position and the PTV centred on the projected predictor data. In 0‐view modality coverage was calculated as the intersection between the CTV centred on the imaged target position and the non‐moving PTV. Similar to dose‐volume histogram, CTV coverage‐volume histograms (defined as CVH) were derived for each patient and treatment modality. The geometric coverages of the 90% and 95% of CTV volume (C90, C95, respectively) were evaluated. Patient‐specific optimal margins (ensuring C95 ≥ 95%) were computed retrospectively. Results: The median ± interquartile‐rage of C90 and C95 for upper lobe lesions was 99.1 ± 0.6% and 99.0 ± 3.1%, whereas they were 98.9 ± 4.2% and 97.8 ± 7.5% for lower and middle lobe tumors. In 2‐view, 1‐view and 0‐view modality, adopted margins ensured C95 ≥ 95% in 70%, 85% and 63% of cases and C95 ≥ 90% in 90%, 88% and 83% of cases, respectively. In 2‐view, 1‐view and 0‐view a reduction in margins still ensured C95 ≥ 95% in 33%, 78% and 59% of cases, respectively. Conclusions: CTV coverage analysis provided an a‐posteriori evaluation of the treatment geometric accuracy and allowed a quantitative verification of the adequacy of the PTV margins applied in CyberKnife LOT treatments offering guidance in the selection of CTV margins.